City Brand Image Building and Its Impact on the Psychological Capital of New Entrepreneurs Following Cultural Construction - Li, Yingji; Hsü, Penghang; Hao, Guanghui; Sun, Kaiyang; Wang, Yahong (Frontiers in Psychology, 2021)
The purpose is to speed up the construction of urban modernization and promote the development of the city innovation economy and the stability of the employment rate. First, the main contents and influencing factors of urban culture construction are introduced. Second, the construction of city cultural images and the social capital of new entrepreneurs are discussed, and the relationship between the two is analyzed. Then, ISM (Interpretative Structural Modeling Method) is put forward, and five influencing factors of city entrepreneurial environments are expounded. A questionnaire survey is designed based on the ISM model, and a nationwide survey of new entrepreneurs is carried out. The survey results show that entrepreneurs of different genders, ages, and educational levels have different degrees of concern for the city image. Among them, the entrepreneurs with different educational levels have the most obvious difference in their attention to the city's cultural image (P<0.05). In addition, public transportation, educational conditions, tourism resources, air quality, and image orientation are the most obvious factors affecting the construction of city brand images (P<0.05). The influence of residents' educational level and investment environment on new entrepreneurs is more prominent. This shows that in the process of shaping the city brand image, the improvement of city culture is helpful for new enterprises. The more perfect the city culture is, the more attractive it will be for highly educated entrepreneurs. The study can help relevant decision-makers to plan the future development direction of the city more accurately and realize the stable development of city brand images.